Indians, settlers & slaves in a frontier exchange economy : the Lower Mississippi Valley before 1783 - Usner, Daniel H. (Published for the Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 1992)
In this pioneering book Daniel Usner examines the economic and cultural interactions among the Indians, Europeans, and African slaves of colonial Louisiana, including the province of West Florida. Rather than focusing on a single cultural group or on a particular economic activity, this study traces the complex social linkages among Indian villages, colonial plantations, hunting camps, military outposts, and port towns across a large region of the pre-cotton south. Usner begins by providing a chronological overview of events in the area from the establishment of a French outpost on the Gulf coast in 1699 to Spanish acquisition of West Florida after the Revolution. He then shows how early confrontations and transactions shaped the formation of Louisiana into a distinct colonial region with a social system based on mutual needs of subsistence. In this area, as in other early colonial regions of North America, Indians, settlers, and slaves interacted with each other and contributed to the regional economy in diverse and fluid ways. After the Lower Mississippi Valley was partitioned between Great Britain and Spain in 1762-1763, argues Usner, the local exchange economy faced new pressures as a result of increased settlement and intensification of export-oriented agriculture along the lower Mississippi River. The flexibility that had characterized cultural and economic interaction began to give way to more rigid boundaries between ethnic groups. Usner's focus on commerce allows him to illuminate the motives in the contest for empire among the French, English, and Spanish, as well as to trace the personal networks of communication and exchange that existed among the territory's inhabitants. By tracing patterns of small-scale, face-to-face exchange, he reveals the economic and social world of early Louisianians and lays the groundwork for a better understanding of later Southern society.